In Vitro and In Vivo Investigation on the Effectiveness of Alginate-Based Gastric Mucosal Protective Gel. (24th August 2022) - Zeng, Hang; He, Muye; Yang, Minyi; Meng, Zhu; Wang, Han; Wang, Chunren
Abstract : Objective . To investigate the feasibility and effectiveness of an alginate-based gastric mucosal protective gel on the gastric ulcer. Methods . (1) In the physical protection model, after GES-1 cell attachment add the gel to transwell chamber, add different concentrations of HCl to the gel. Absorbance was measured to assess proliferation and images of the cells migrating into the wound were taken; then the migration rate of the cells was quantified by comparing images. (2) In the gastric ulcer model, excise the gastric mucosal of SD rats; the gel and fixative were applied on the artificial ulcer immediately. Dissect rats after 10 days, and calculate the wound healing rate and analyzed histology changes. Results . The effect of hydrochloric acid on cells in the lower layer was significantly reduced after the use of gastric mucosal protection gel. The protective gel had an isolation effect on different concentrations of acid. A number of GES-1 were significantly higher than those in the control group at 24 h to 72 h (P < 0.01 ). The migration was observed compared with the control group. The average healing rate of ulcer in the gel group was about 50%, and the control group was about 30%. Inflammation occurred in all wound regions after ten days. In the gel group, inflammatory infiltration depth was lower than that of the control, and part of SD rats' new muscle layer appeared without inflammatory infiltration. The connective tissue proliferation promoted tissue repair. In the control group, necrosis marginal, mucosal hyperplasia, marginal lymphocyte aggregation, and bleeding were observed. Conclusion . This novel gel mainly has an isolating and shielding effect to prevent the wound from being exposed to gastric acid for a long time, and it can reduce the inflammatory reaction on the wounds to promote the healing of the ulcer. The gastric mucosal protective gel cannot only promote the speed of wound healing but also improve the quality of wound healing.